Bioderived and degradable polymers for transient electronics. Issue 4 (19th May 2021) - Uva, Azalea; Lin, Angela; Babi, Jon; Tran, Helen
Abstract: As single‐use electronics become more prevalent in our society, a shift towards devices with alternative disposal fates will be required to address rising levels of electronic and plastic waste. Adopting transient electronics is one solution for inadvertent litter of future single‐use electronics as they are designed to automatically break down in environmental conditions after their intended use. However, the selection of appropriate source materials to make these transient devices is vital to ensure environmental compatibility. This mini‐review aims to highlight recent advancements in bioderived polymers that can be used as substrates or encapsulants, the largest weight percentage in a device, in transient electronics. The chemical and biological degradation of these bioderived polymers is also discussed to present potential non‐toxic byproducts and factors affecting degradation rates. Lastly, the potential outlook of transient electronics in biomedical, environmental, and consumer applications are proposed to demonstrate the wide scope of opportunities to be explored. © 2021 Society of Chemical Industry (SCI).